1992
DOI: 10.1007/bf01542257
|View full text |Cite
|
Sign up to set email alerts
|

Paraphilias: A double-blind crossover comparison of clomipramine versus desipramine

Abstract: A relationship has been suggested between clinical presentation of paraphilias and obsessive-compulsive disorder (OCD) with respect to the unwanted repetitive nature and insight into the irrationality of the paraphiliac behavior. This has led to speculation that paraphiliac disorders might belong to an "obsessive compulsive spectrum." To address this issue, and because of the striking selective benefit of serotonin reuptake blocking antidepressants (such as clomipramine) in the treatment of OCD, 15 paraphiliac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…A number of small studies and case reports (67)(68)(69)(70)(71)(72) have found treatment with antidepressants helpful for patients with paraphilias. These studies have included patients for whom tricyclics or lithium was used (70).…”
Section: Newer Hormonal Therapies and Serotonergic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of small studies and case reports (67)(68)(69)(70)(71)(72) have found treatment with antidepressants helpful for patients with paraphilias. These studies have included patients for whom tricyclics or lithium was used (70).…”
Section: Newer Hormonal Therapies and Serotonergic Agentsmentioning
confidence: 99%
“…These studies have included patients for whom tricyclics or lithium was used (70). However, most of the more recently reported successes have been with selective serotonin reuptake inhibitors (SSRIs) (67)(68)(69).…”
Section: Newer Hormonal Therapies and Serotonergic Agentsmentioning
confidence: 99%
“…In doing so he neglected to consider whether violence would continue to be under-predicted if one of the custody options were to release dangerous sex offenders (DSOs) to the community on the condition that they abide by a set of restrictions that might dictate the place of their residence and the terms of treatment, parole, and participation in a monitoring program. This is an important oversight because (1) a number of conditions have been found to be effective for reducing the risk of sexual recidivism (Federoff, Wisner-Carlson, Dean, & Berlin, 1992;Hall, 1995aHall, , 1995bKruesi, Fine, Valladares, Phillips, & Rapoport, 1992;Land, 1995); (2) for each DSO, some clinical assessment needs to be made at some point as to whether the imposition of these or other conditions might signi®cantly reduce his recidivism risk (Covington, 1997); (3) commitment statutes require that DSOs must be conditionally released when it may be expected that their recidivism risk will be reduced below the commitment standard by adhering to a set of alternatives that are less restrictive than total con®nement (Covington, 1997). Doren therefore did not portray the predictive tasks associated with DSO cases as being as complex as they actually are.…”
Section: Discussionmentioning
confidence: 99%
“…Relations have been suggested between clinical presentation of paraphilias and obsessive-compulsive disorder [Kruesi et al, 1992], and of impulse-control disorders and bipolar disorder as well [McElroy et al, 1996]. Moreover, a monoamine hypothesis for the pathophysiology of paraphilic disorders has been put forward [Kafka, 2003], In the naïve opinion of a nonpsychiatrist like me, SSRIs could be adequate for the present case on at least a 'quick fixing' ground, and in order to bridge the time pending a specialised consultation.…”
Section: Discussionmentioning
confidence: 99%